Energy, ecology, and global climate warming - Matsevity, Yu.M.; Shubenko, A.L.; Kanilo, P.M.; Solovey, V.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
Based on the fact that the current global warming bears the anthropogenic-ecological character, the authors believe that a strategic solution to the problem is to stabilize planet's climate by the improvement of its biosphere, climaterecovery functions of the global biota, and the greening of all spheres of the human activity.